2014
DOI: 10.3906/biy-1406-93
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells: emerging actors in both basic and clinical cancer research

Abstract: IntroductionOver the past 50 years, many disease that cause death have dramatically decreased. Nevertheless, cancer deaths continue (Leaf, 2013). The International Agency for Research on Cancer, the specialized cancer agency of the World Health Organization, released the latest data on cancer incidence, mortality, and prevalence worldwide (Ferlay et al., 2013). According to GLOBOCAN 2012, an estimated 14.1 million new cancer cases and 8.2 million cancer-related deaths occurred in 2012, compared with 12.7 milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…Furthermore, it has also been demonstrated that cell surface markers could be dynamically and reversibly expressed by tumorigenic cells [46]. Therefore, it is clearly insufficient to define a cancer stem cell based solely on surface markers [11].…”
Section: Cell Surface Markersmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, it has also been demonstrated that cell surface markers could be dynamically and reversibly expressed by tumorigenic cells [46]. Therefore, it is clearly insufficient to define a cancer stem cell based solely on surface markers [11].…”
Section: Cell Surface Markersmentioning
confidence: 99%
“…SP cells constitute a subpopulation of cancer cells that can efficiently efflux the fluorescent DNA binding dye, Hoechst 33342 and ATP binding cassette transporter [14]. Although the use of Hoechst 33342 dye enables identification of Hoechst-negative CSC SPs, the possible toxicity of the dye may cause side effects during cell sorting [11]. Small differences in cell densities, dye concentrations and staining timings may affect the phenotype of the SP cells [14].…”
Section: Dye Exclusion Assaysmentioning
confidence: 99%
See 3 more Smart Citations